Sosialisasi Pemahaman Korban Judi Online Dan Upaya Pencegahan Pada Anak Remaja Tingkat Menengah - Kurniawan, Dadang; Muhamad Akbar; Fedi Kasdinata; Firmansyah, Muhammad Ridho; Hendra Kurniawan; Devina Ninosari; Hermana, M. Arafat; Sandi Aprianto; Khairil; Devi Sartika (Jurnal Pengabdian Mitra Persada, 2025)
The KKN activity with the theme "Socialization of Online Gambling Prevention for Teenagers at Bengkulu State High School 8 is motivated by the rise of online gambling which can damage the nation's young generation. The high interest in online gambling that has hit the young generation today has encouraged the Dehasen Bengkulu KKN Group to carry out outreach on the prevention of online gambling which was held at State High School 8 Bengkulu. The aim of this activity is to increase students' awareness in tackling online gambling at State High School 8 Bengkulu. In this socialization activity, the methods used were lectures, discussions and questions and answers. This socialization was attended by 35 students. The approach taken is to provide understanding and explanation of the material and invite participants in outreach activities to discuss the prevention of online gambling among teenagers. The results of the socialization organized by the Community Service Team show that this activity has been carried out well. This is proven through the active involvement of participants in taking part in socialization, including their participation in discussions and question and answer sessions after the delivery of material by the Dehasen KKN Group.